2004
DOI: 10.1016/s0002-9440(10)63247-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrity of Cell-Cell Contacts Is a Critical Regulator of TGF-β1-Induced Epithelial-to-Myofibroblast Transition

Abstract: Injury of the tubular epithelium and TGF-beta1-induced conversion of epithelial cells to alpha-smooth muscle actin (SMA)-expressing myofibroblasts are key features of kidney fibrosis. Since injury damages intercellular junctions and promotes fibrosis, we hypothesized that cell contacts are critical regulators of TGF-beta 1-triggered epithelial-to-mesenchymal transition (EMT). Here we show that TGF-beta 1 was unable to induce EMT in intact confluent monolayers, but three different models of injury-induced loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
228
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(250 citation statements)
references
References 63 publications
19
228
3
Order By: Relevance
“…Since these antagonists are critical in ensuring the regulation of Smadmediated gene transcription, a fine balance must be achieved in order to match cellular demands. It is of no surprise that diminished levels of co-repressors are observed in animal models of obstructive nephropathy and diabetes [67]. Smad ubiquitination regulatory factor-2 (Smurf2) is an ubiquitin ligase that specifically targets certain members of Smad proteins for degradation, including Ski, SnoN and TGIF [63].…”
mentioning
confidence: 99%
“…Since these antagonists are critical in ensuring the regulation of Smadmediated gene transcription, a fine balance must be achieved in order to match cellular demands. It is of no surprise that diminished levels of co-repressors are observed in animal models of obstructive nephropathy and diabetes [67]. Smad ubiquitination regulatory factor-2 (Smurf2) is an ubiquitin ligase that specifically targets certain members of Smad proteins for degradation, including Ski, SnoN and TGIF [63].…”
mentioning
confidence: 99%
“…Studies have shown that TGF-β 1 stimulates lung microvascular endothelial cells to produce ET-1, which promotes smooth muscle cell proliferation (Star et al 2008). Furthermore, TGF-β 1 plays an initiation and facilitation role in the process of endothelium-smooth muscle transformation (Masszi et al 2004). In our study, higher TGF-β 1 levels in the lung tissue of the MCT group may be due to elevated shear force, which can cause increased release of TGF-β 1 from the endothelium (Cucina et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Submesothelial stromal cells, ovarian thecal cells, pericytes, hepatic perisinusoidal cells (hepatic stellate cells), pancreatic stellate cells or reactive macrophages have been also proposed as cells capable of expressing myofibroblastic phenotypes under pathological conditions [33][34][35][38][39][40] . Furthermore, it has been reported that renal epithelial cells may transdifferentiate into myofibroblastic cells in renal interstitial fibrosis [41][42][43][44] . It thus appears that so-called "myofibroblastic cells" in fibrotic lesions are generated from heterogeneous cell populations 45 .…”
Section: Myofibroblastsmentioning
confidence: 99%
“…2); these cytoskeletons represent useful markers of myofibroblastic differentiation 33,35 . It has been recently postulated that EMT, in which renal epithelial cells acquire myofibroblastic phenotypes, may contribute to the progressive renal fibrosis [41][42][43][44]60 . In the chronic model, it has been found that a number of cuboidal or flattened, single-or multi-layered epithelia in the fibrotic areas show a strong immunoexpression to α-SMA (Fig.…”
Section: Myofibroblasts In the Cisplatin-induced Rat Chronic Modelmentioning
confidence: 99%
See 1 more Smart Citation